2017
DOI: 10.1007/s40843-017-9107-x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-encapsulated polymeric nanoparticles for metastatic osteosarcoma cells treatment

Abstract: Osteosarcoma is a high-class malignant bone cancer with a less than 20% five-year survival rate due to its early metastasis potential. There is an urgent need to develop a versatile and innoxious drug to treat metastatic osteosarcoma. Curcumin (Cur) has shown its potential for the treatment of many cancers; however, the clinical implication of native curcumin is severely hindered by its intrinsic property. In this study, a mixed system of monomethoxy (polyethylene glycol)-poly(d, l-lactide-co-glycolide)/poly(ε… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Curcumin has been demonstrated to have anti-neoplastic properties and cell proliferation inhibition in tumoural cells [23,24]. It is described that the viability of human osteosarcoma cells U2OS was reduced upon curcumin treatment [97].…”
Section: Cell Proliferation and Cell Viability Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin has been demonstrated to have anti-neoplastic properties and cell proliferation inhibition in tumoural cells [23,24]. It is described that the viability of human osteosarcoma cells U2OS was reduced upon curcumin treatment [97].…”
Section: Cell Proliferation and Cell Viability Assaysmentioning
confidence: 99%
“…Curcumin inhibited the growth of all osteosarcoma cell lines in addition to inhibiting their migration [23]. Wang et al [24] demonstrated that free curcumin and its encapsulated form in a mixed system of biopolymers were able to inhibit the proliferation, migration, and invasion of osteosarcoma cells. Furthermore, suggest that curcumin has the potential to be a new chemotherapeutic agent in the treatment of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…4c, the combination of 3-MA@Ag@MSNs and RT killed all cells in the group. Specifically, transwell invasion assay was performed to evaluate the antimigration effect of combination therapy [39] (Fig. 4d).…”
Section: In Vitro and In Vivo Anti-tumor Effect Evaluationmentioning
confidence: 99%
“…Several approaches have been pursued to overcome barriers to using curcumin since the solubility of curcumin in water is very low and the rate of degradation in an alkaline state is very high. The use of delivery systems such as hydrogels, liposomes, dendrimers, and micro-/nanoparticles to encapsulate the hydrophobic curcumin in its hydrophobic core has been investigated [ 88 ]. The amphiphilic peptide C18GR7RGDS is a nanoparticle carrier of curcumin in an aqueous solution with self-assembly characteristics in water and phosphate-buffered saline that shows a selective cytotoxicity effect against osteosarcoma cells compared to normal cells.…”
Section: Curcumin Delivery Systems To Osteosarcoma Cellsmentioning
confidence: 99%
“…Curcumin encapsulated in natural biodegradable polyphenol hydrophilic copolymer y (polyethylene glycol)-poly(D,L-lactide-co-glycolide)/poly( ε -caprolactone) (mPEGPLGA/PCL) and (polyvinyl alcohol-polyethylene glycol − PVA-PEG) showed a synergic cytotoxic and anti-proliferation effect in osteosarcoma cells by decreasing the expression of CMYC, as a major protooncogene. Furthermore, this formulation can decrease the expression levels of MMP7, which correlates with metastatic features in cancers, thus preventing the invasion of osteosarcoma cells [ 88 , 97 ].…”
Section: Curcumin Delivery Systems To Osteosarcoma Cellsmentioning
confidence: 99%